2004
DOI: 10.1590/s0085-56262004000400018
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos da temperatura no desenvolvimento, fecundidade e longevidade de Gargaphia torresi Lima (Hemiptera, Tingidae)

Carlos Alberto Domingues da Silva

Abstract: ABSTRACT. Effects of temperature on the development, fecundity, and longevity of Gargaphia torresi Lima (Hemiptera, Tingidae). The development of Gargaphia torresi Lima on cotton leaves was studied in bioclimatic chambers at 20, 23, 25, 28 The values of longevity and fecundity were inversely proportional with increase of the temperature. The thermal constant (K) and theoretical lower threshold temperature of development (Tb) were estimated by Reamur law and intercession method of the X, respectively. The th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
5
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 13 publications
4
5
0
2
Order By: Relevance
“…The longer fifth instar was obtained for other Tingini, as Gargaphia torresi Lima, 1922(Silva, 2004, Leptopharsa heveae Drake & Poor, 1935(Cividanes et al, 2004, Stephanitis pyrioides (Scott, 1874) (Braman Tab. II.…”
Section: Discussionmentioning
confidence: 96%
“…The longer fifth instar was obtained for other Tingini, as Gargaphia torresi Lima, 1922(Silva, 2004, Leptopharsa heveae Drake & Poor, 1935(Cividanes et al, 2004, Stephanitis pyrioides (Scott, 1874) (Braman Tab. II.…”
Section: Discussionmentioning
confidence: 96%
“…Segundo Kohno & Bui Thi (2005), insetos herbívoros, como as espécies de Dysdercus, têm sua ocorrência associada à de suas plantas hospedeiras. Entre os fatores abióticos, a temperatura tem papel de destaque, influenciando diretamente o desenvolvimento, reprodução e comportamento dos insetos, e indiretamente através do alimento (Silva 2004;Chagas Filho et al 2005;Vivan & Panizzi 2005). Segundo Silveira Neto et al (1976), a exigência térmica de uma espécie determina a velocidade de seu desenvolvimento, o número de gerações por ano e a prolificidade.…”
Section: Resumo Efeitos Da Temperatura E Do Alimento No Desenvolvimeunclassified
“…Many papers have been published on the use of PANI for the protection of metals against corrosion. [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] Mengoli et al 10 found that the paints containing PANI offer high corrosion-resistant coating. Wessling and Posdorfer 11,12 reported that the corrosion potential for PANI-coated metals significantly shifts toward noble potentials and corrosion current decreases.…”
Section: Introductionmentioning
confidence: 99%